ETTI MERINOS – KAZAKHSTANI EXPORT-ORIENTED MEAT BREAD - Torekhanov Aibyn Adepkhanovish; Zhumadillaev Nurzhan Kudaibergenovich (Academic Journal of Physical and Chemical Sciences, 2021)
Sheep breeding in Kazakhstan is a traditional branch of animal husbandry. The development of the industry is facilitated by the presence of large areas of pasture lands, as well as the existing valuable gene pool of breed resources, created by national selection and long-term work of scientists-breeders. The republic has great potential for the further development of sheep breeding industry and is able not only to meet the population’s need for mutton, but also to become a major exporter. The restoration and further development of domestic sheep breeding should be based on rational use of genetic potential of animals and natural pastures of the country for the cost-effective production of high quality sheep products that meet international standards. The article deals with the development of fine-wool sheep breeding in Almaty, Zhambyl and South Kazakhstan regions, improvement of meat characteristics of the South Kazakh merino. The experience of using "etti merino" rams-producers in farms of Turkestan region showed that meat merino rams have a positive effect on meat productivity of the South Kazakh merino, and at the same time do not worsen their wool characteristics. The information on the population number of sheep of "Etti Merino" breed for 2020, the class composition of the ewes on farms, productivity of rams-producers in a number of generations, assessment of the quality of the offspring of 6-7 month old rams, wool productivity of the breeding groups of female sheep are presented.